A study on the factors determining adoption of computerized accounting system in public hospital: The case study of three district hospitals in Arusha Region - Fortunata, Alfredy S. (Mzumbe University, 2024)
A dissertation presented to Mzumbe University in partial/fulfillment of the requirement for the award of Master’s Degree of Science in Accounting and Finance of Mzumbe University